2020
DOI: 10.1016/j.molp.2020.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Lectin Receptor-like Kinase Phosphorylates the Bacterial Effector AvrPtoB to Dampen Its Virulence in Arabidopsis

Abstract: Plasma membrane-localized receptor-like kinases (RLKs) perceive conserved pathogen-associated molecular patterns (PAMPs) in plants, leading to PAMP-triggered immunity (PTI). The Arabidopsis thaliana lectin RLK LecRK-IX.2 has been shown to regulate the bacterial flagellin-derived peptide flg22-induced PTI.Here, we discover that Pseudomonas syringae effector AvrPtoB targets LecRK-IX.2 for degradation, which subsequently suppresses LecRK-IX.2-mediated PTI and disease resistance. However, LecRK-IX.2 can interact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Another L-type lecRLK encoding gene ( AtLPK1 ) is related to elevated resistance to Botrytis cinerea [ 38 ]. In addition, the L-type lecRLK LecRK-IX.2 not only can activate the immune responses, but also can phosphorylate the bacterial effector AvrPtoB and thereby potentially can reduce its virulence [ 12 , 39 ]. Several reports showed that L-type LecRLKs are also involved in plants’ responses to abiotic stresses stimuli and plants’ developmental processes [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another L-type lecRLK encoding gene ( AtLPK1 ) is related to elevated resistance to Botrytis cinerea [ 38 ]. In addition, the L-type lecRLK LecRK-IX.2 not only can activate the immune responses, but also can phosphorylate the bacterial effector AvrPtoB and thereby potentially can reduce its virulence [ 12 , 39 ]. Several reports showed that L-type LecRLKs are also involved in plants’ responses to abiotic stresses stimuli and plants’ developmental processes [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Membrane localized receptor-like kinases (RLKs), together with other signal receptors like phytochromes, act as the first site of signal perception, which allows the plants to communicate between cells and to respond to changes in their environment [1,2]. Lectin receptor-like protein kinase (LecRLK) family is a group of RLKs that have been shown to play several vital roles in plant pathogenic defense, symbiotic association, insect feeding response, innate immunity and different abiotic stress responses, such as low temperature and high salinity [3][4][5][6][7][8][9][10][11][12][13][14]. LecRLKs were firstly discover and examined in Arabidopsis thaliana [15], and were later isolated in a few important food crops, such as Oryza sativa [16], Pisum sativum [17], Solanum lycopersicum [10], Pyrus bretschneideri [2] and Solanum tuberosum [14].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies showed that ubiquitination-mediated protein degradation play important role in pathogen-host interaction. For example, the effector AvrPtoB, an E3 ligase from Pseudomonas syringae, promotes the degradation of positive plant immunity proteins, including lectin RLK LecRK-IX.2 and EXO70B1, to enhance the Pto DC3000 virulence (Wang et al 2019b;Xu et al 2020). In addition, LecRK-IX.2 reversely phosphorylates AvrPtoB to reduce its E3 ligase activity (Xu et al 2020).…”
Section: Ubiquitination-mediated Regulation Of Secreted Effectorsmentioning
confidence: 99%
“…For example, the effector AvrPtoB, an E3 ligase from Pseudomonas syringae, promotes the degradation of positive plant immunity proteins, including lectin RLK LecRK-IX.2 and EXO70B1, to enhance the Pto DC3000 virulence (Wang et al 2019b;Xu et al 2020). In addition, LecRK-IX.2 reversely phosphorylates AvrPtoB to reduce its E3 ligase activity (Xu et al 2020). In M. oryzae-rice interaction, the effector AvrPiz-t interacts with two RING-type E3 ligases, AVRPIZ-T INTERACTING PROTEIN 6 (APIP6) and APIP10, to suppress their ubiquitin ligase activities and promote their degradation.…”
Section: Ubiquitination-mediated Regulation Of Secreted Effectorsmentioning
confidence: 99%
“…The full virulence function of AvrPtoB requires in planta phosphorylation at serine-258, which is catalyzed by the Snf1-related kinase SnRK2.8 [ 355 , 356 ]. This can be counteracted, however, by the interaction of AvrPtoB with either Pto kinase or the lectin receptor-like kinase LecRK-IX.2, which phosphorylate AvrPtoB at threonine-450 or serine-335, respectively, to compromise the virulence-promoting E3 ubiquitin ligase activity of the T3SE [ 357 , 358 ]. For AvrPto, phosphorylation at serine-147 and serine-149 is required for its full virulence-promoting activity on susceptible tomato plants [ 359 , 360 ].…”
Section: Context Matters: T3se Activation In Eukaryotic Hostsmentioning
confidence: 99%